Fabrication and characterization of porous polycaprolactone scaffold via extrusion-based cryogenic 3D printing for tissue engineering. (15th October 2019) - Zhang, Wancheng; Ullah, Ismat; Shi, Lei; Zhang, Yu; Ou, Hao; Zhou, Jinge; Ullah, Muhammad Wajid; Zhang, Xianglin; Li, Wenchao
Abstract: Earlier reports of fabricating 3D porous PCL scaffolds for tissue engineering applications were overshadowed by several limitations such as additional molds cost, relatively low efficiency, and lacking process control. In present study, combined extrusion-based cryogenic 3D printing (ECP) (−20 °C) and subsequent freeze-drying approaches were employed to facilely fabricate polycaprolactone (PCL) scaffolds, with high porosity and fidelity. Freeze-drying caused shrinkage of the scaffolds along X, Y, and Z -axes to some extent. The porosities of CP600, CP800, and CP1000 were found to be 64.0 ± 1.2%, 70.1 ± 1.3%, and 74.3 ± 0.6%, respectively. The fabricated scaffolds were characterized for various structural features and compared with the ones fabricated through traditional extrusion-based melt 3D printing (EMP). The crystallinity of PCL in ECP scaffolds was lower (57.1 ± 2.2%) than EMP scaffolds (69.8 ± 1.3%). The ECP scaffolds showed high alkaline degradation, but low compression properties. The ECP scaffolds promoted the adhesion and proliferation of MCT3T-E1 cells with well-spread morphology on the porous filaments. Together, these features justify the suitability of printed PCL scaffolds for potential TE applications. Graphical abstract: Unlabelled Image Highlights: Facile fabrication of porous PCL 3D scaffolds via extrusion-based cryogenic 3D printing and freeze-drying. Obtained highly porous and amorphous crystalline scaffolds. The scaffolds possess improved degradation behavior and desired compression property for tissue engineering applications. Highly biocompatible scaffolds in terms of improved cell adhesion, proliferation, and spreading.